2016
DOI: 10.1186/s12917-016-0912-4
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin as a biomarker in equine chronic pneumopathies

Abstract: BackgroundProcalcitonin (PCT), a precursor protein of the hormone calcitonin, is a sensitive inflammatory marker in human medicine, which is primarily used for diagnosis of bacterial sepsis, but is also useful in diagnosis of exacerbation of asthma and COPD. In this study, PCT was evaluated as a potential biomarker for different chronic pneumopathies in the horse using an equine specific ELISA in comparison to established clinical markers and different interleukins.Sixty-four horses were classified as free of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
3
4
0
Order By: Relevance
“…In this study, we found differences between healthy vs. total colic horses at admission time. Our results are in line with previous studies that reported differences between sick vs. healthy bovine [16,18,20,25], horses [14,15,19,24,26] and foals [13] affected by different diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found differences between healthy vs. total colic horses at admission time. Our results are in line with previous studies that reported differences between sick vs. healthy bovine [16,18,20,25], horses [14,15,19,24,26] and foals [13] affected by different diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Procalcitonin (PCT) has been studied over the last few years as a biomarker of inflammation and/or infection, both in human [22] and in large animal species [13][14][15][16][17][18][19][20][21][23][24][25][26]. The aims of this study were to evaluate the potential differences in plasma PCT concentrations between healthy vs. SIRS-negative vs. SIRS-positive horses in order to understand if PCT can be a useful biomarker to distinguish between these conditions and drive clini-cal decisions of equine veterinarians and SIRS score in order to verify if this biomarker could be useful for the evaluation of SIRS severity.…”
Section: Discussionmentioning
confidence: 99%
“…No animals were diagnosed with hypercalcemia in our study, so the possibility that the increase in PCT was based on hypercalcemia and increased calcitonin was excluded, supporting Barton et al [23], who indicated that PCT increased independently of serum calcium levels during bacterial infections. This proved that PCT was not only important as a precursor protein of calcitonin responsible for regulating blood calcium levels but also had its own role in the body independent of calcium, when bacterial infections occur.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, all the published papers dedicated to PCT detection in animals are refer to use of commercially available ELISA kits that are not fully validated in the target species, are expansive, and useful only for research purposes 72 . Notably, no analytical parameters are reported in literature for the equine PCT ELISA kits, and the only ones present are referred to the use of human anti-PCT antibodies, due to the current lack of specific anti-equine antibodies [73][74][75] . At the same time, acceptable analytical parameters are reported only for one type of canine PCT ELISA kit [68][69]76 .…”
Section: Introductionmentioning
confidence: 99%
“…72 Notably, no analytical parameters are reported in the literature for equine PCT ELISA kits, and the only ones present referred to the use of human anti-PCT antibodies, due to the current lack of specic anti-equine antibodies. [73][74][75] At the same time, acceptable analytical parameters are reported only for one type of canine PCT ELISA kit. 68,69,76 Based on the lack of fully reliable and practical tests, the aim of this work is to develop an innovative analytical assay, for the detection of PCT in veterinary species, by combining the practicality of commercial ELISA kits with the advantages of MIPs.…”
Section: Introductionmentioning
confidence: 99%